Photonic Jets and Single‐Photon Emitters. Issue 11 (31st August 2022) - Ristori, Andrea; Felici, Marco; Pettinari, Giorgio; Pattelli, Lorenzo; Biccari, Francesco
Abstract : Photonic jets (PJs) obtained by illuminating a dielectric microsphere have recently shown to provide an efficient and cost‐effective means of laser‐writing and localizing single‐photon emitters with sub‐diffraction precision. The fabrication technique relies on the photoinduced formation of GaAsN quantum dots (QDs) that are self‐aligned to the microsphere, which in turn enhances the collection efficiency of their emission. Similarly, the angular magnification introduced by a microsphere placed on top of two close emitters allows to detect and resolve their separation below the diffraction limit by analyzing their angular emission pattern in momentum space. Along with a brief review of the two methods, a systematic numerical study on the formation and properties of PJs to streamline the optimization of the fabrication process is presented. Abstract : Photonic jets (PJs), highly intense electromagnetic beams with sub‐wavelength lateral extent, can be obtained by illuminating dielectric microspheres. PJs allow to laser‐write single‐photon emitters and enhance the collection efficiency (×7.3 with 0.7 numerical aperture) and the optical resolution (×2.3) of the system. After a review of these applications of PJs, a systematic numerical investigation of their properties is presented.